Utilization of Terrarium Media in Science Learning to Improve Understanding Ecosystem and Students' Environmental Awareness - Khairul Amri; Fitri Adifa (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This research is motivated by the low cognitive learning outcomes and environmental awareness among students due to ecosystem topics traditionally being delivered in an abstract and theoretical manner. This study, entitled